The role of orthopedic screws threads properties on the success of femoral fracture fixation. (September 2022) - Torabi, Masoud; Khorramymehr, Siamak; Nikkhoo, Mohammad; Rostami, Mostafa
Stress shielding is created following a reduction in bone density due to the reduction or elimination of mechanical stimuli and the resultant stresses around the implant site in bone tissue. Increased stress shielding can cause the implant or screw to detach or loosen over time, which in turn can lead to severe side effects such as pain, infection, necrosis, and dysfunction. The geometric shape and characteristics of the screws are among the most important factors involved in creating the stress shielding. Hence, the current study aimed to evaluate the influence of bone screw design parameters (i.e., thread profile, thread pitch, screw diameter, and elastic modulus) on stress shielding around the standard screws after implantation in the proximal femur using a viscoelastic finite element modelling. Stress transfer parameters (STP) and strain energy density transfer parameters (SEDTP) were used to evaluate the stress shielding and the risk of screw loosening using the finite element method. This study was performed on screws with titanium and beta-titanium alloy materials as well as HB, HC, and HD ISO threads that are considered as implants for fracture fixation. The results indicated that the HB ISO thread has the least stress shielding and looseness. It was also found that reducing the modulus of elasticity of the screws, increasing the number of threads per screw, reducing the pitch of the screws and the diameter of the screws shaft reduce the amount of the stress shielding and loosening of the screws. This study can provide surgeons with valuable quantitative data for selecting the effective types of screws for bone fracture fixations towards enhanced clinical outcomes.